A Review on Perspectives of Educators, Students and Employers on Hospitality Internships - Mohanty, Sasmita; B Pradhan, Bibhuti (International Journal of Psychosocial Rehabilitation, 2025)
For hospitality education, the internship is one of the most common forms of experiential learning. But to be effective it needs teachers, employees, and educators to collaborate. One of the most important ways to help graduates plan for their jobs, and life, is by incorporating practical skills, whether it be internships, apprenticeships, or even outsourcing. Not only does a hands-on approach to learning help students develop a deeper understanding of their theoretical knowledge, but it’s also their first step into exploring an environment that could affect the rest of their lives, which is why having the interaction truly count is important. This paper identifies the role and value of hospitality education internships. The benefits and negatives are addressed from the viewpoints of the three owners, and an aggregate evaluation is explored. The article concludes by presenting suggestions for future study.